‘I’m not Sherlock Holmes’: Suspicions, secrecy and silence of transplant professionals in the human organ trade - Ambagtsheer, Frederike (European journal of criminology, 2020)
This article presents the results of a qualitative interview study amongst 41 Dutch transplant professionals. The overarching aim was to acquire in-depth understanding of transplant professionals’ experiences with and attitudes towards patients who purchase kidneys. We found that transplant professionals occasionally treat patients who are suspected of kidney purchases abroad. However, they turn a blind eye to their patients’ suspected purchases. Secrecy and silence function as a tacit agreement between patients and their caregivers that keeps the subject of kidney purchase at a safe distance and allows transplant professionals to ignore its suspected occurrence. They thus participate in the building of walls of secrecy and silence in the organ trade.